An Application of Physical Layer Security to Protect NOMA-Backscatter Communication - Tran, Truc Thanh; Tran, Diem-Phuc (Journal of Technical Education Science, 2025)
This paper explores the enhancement of physical layer security in a communication model that integrates backscatter communication and Non-Orthogonal Multiple Access (NOMA) technology. The system involves two users sharing a common receiver, with a potential eavesdropper attempting to intercept the transmission. The study incorporates Rayleigh fading in backscatter channels and derives the theoretical probability of secure transmission capacity, providing a framework for analyzing security performance. To validate the theoretical results, Monte Carlo simulations are conducted, showing strong consistency between theoretical predictions and simulated outcomes. This research highlights the potential of combining backscatter communication with NOMA to improve data security and transmission efficiency, particularly in wireless environments prone to adversarial threats. The findings contribute to the understanding of how these technologies can work together to enhance security in next-generation communication systems, such as IoT and 5G networks, where secure and energy-efficient data transmission is critical. The paper offers new insights into physical layer security techniques and provides a foundation for future research in secure communication models involving emerging technologies.